Analisis Strategi Pemasaran dalam Meningkatkan Volume Penjualan pada UMKM Cake Pisang Raja Impian Tuban - Anggi Dian Lestari; Jojok Dwiridotjahjono (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study was conducted with the aim of knowing and analyzing the marketing strategy in increasing sales volume in the UMKM Cake Pisang Raja Raja Impian Tuban business. The sampling method was carried out by purposive sampling by analyzing the 7P marketing mix strategy (product, price, place, promotion, process, people, physical evidence) and STP (segmenting, targeting, and positioning) that had been implemented. This research was analysed using a descriptive method using SWOT analysis (Strength, Weakness, Opportunity, Threat). SWOT analysis is used to evaluate the strengths and weaknesses of the company's internal environment as well as the opportunities and threats that are the company's external environment. SWOT analysis can produce several alternative strategies that can be implemented in making decisions for future businesses in order to develop and adjust to the business environment. The results of this study indicate that the UMKM Raja Banana Cake Dream Tuban business has Strengths 2.66 , Weaknesses 0.61 , Opportunities 2.10 , and Threats 0.72 . So that in the SWOT analysis diagram the UMKM Pisang Raja Impian Tuban Cake is in quadrant 1 (one) position which supports aggressive strategies on the various opportunities and strengths it has.